Conservative Politicians and Voting on Same-Sex Marriage - Björn Kauder; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine whether conservative politicians are less likely to support same-sex marriage when they run for office in safe districts using new data based on a roll-call vote in the national German parliament. The results show that the margin of the majority for the incumbent in the previous election was a strong predictor for supporting same-sex marriage. When the majority increased by one percentage point, the likelihood of voting in favour of same-sex marriage decreased by around 1.3 percentage points. We conjecture that politicians are election-motivated – even when submitting roll-call votes on a matter of conscience.
Keywords: D72; D78; P16; 330; same-sex marriage; gay rights; safe districts; vote margins; supermajorities; roll-call votes